Praise Communication Network On Social Media (Read Map Of Millennial Era) - Agoes Moh. Moefad; Sokhi Huda; Maulidatus Syahrotin Naqqiyah (FAKULTAS DAKWAH UIN SALATIGA, 2023)
The development of communication and information technology has facilitated all human activities, including religion. New media, such as social media, has a flexible context that makes people easily believe even though they realize the level of truth is not guaranteed. This research examines the patterns and understanding of religion in millennial communities in Surabaya. This research uses McLuhan's technological determinism theory with a descriptive qualitative method. The research findings show that the religious patterns of millennial society have shifted at this time, namely religion is carried out regardless of the scientific chain. In addition, interest in religion is also based on interesting content on social media. As for the context of understanding religion through communication networks, people understand religion tends to be brief and fanatical.